The Inclusion of Children’s Rights in the Islamic Studies Curricula of Saudi Arabia: (Analytical Study) - Aldossari , Ali (Dirasat: Human and Social Sciences, 2022)
The study investigates the inclusion of children’s rights in the Islamic studies curricula for the upper primary grades in Saudi Arabia for the 2020 academic year. Content analysis was performed using a coding table comprised of 39 paragraphs categorized according to the five main fields of children’s rights, the rights related to social, intellectual, psychological, economic and political aspects. The results of the study revealed that social rights were shown to be included most frequently, followed by intellectual rights; psychological, economic, and political rights were included less often. All were randomly distributed in the examined textbooks, as they did not take into account the cognitive progression, integration, and continuity when presenting children’s rights. There are no statistically significant differences (α≤0.05) between the percentages of each of the children’s rights fields included in Islamic Studies curricula at the primary stage in Saudi Arabia due to the grade level variable. Accordingly, the study recommends preparing and developing the Islamic studies curricula according to a purposeful scientific methodology. The curricula should include explicit or implicit children’s rights with appropriate percentages and take into account the progression and integration when building cognitive experiences and designing enriching activities that integrate the contents of cognitive structure and children’s rights.